Historical Spatial and Temporal Climate Trends in Southern Ontario, Canada - Wazneh, Hussein; Arain, M. Altaf; Coulibaly, Paulin (Journal of Applied Meteorology and Climatology, 2017)
Abstract Spatial and temporal trends in historical temperature and precipitation extreme events were evaluated for southern Ontario, Canada. A number of climate indices were computed using observed and regional and global climate datasets for the area of study over the 1951–2013 period. A decrease in the frequency of cold temperature extremes and an increase in the frequency of warm temperature extremes was observed in the region. Overall, the numbers of extremely cold days decreased and hot nights increased. Nighttime warming was greater than daytime warming. The annual total precipitation and the frequency of extreme precipitation also increased. Spatially, for the precipitation indices, no significant trends were observed for annual total precipitation and extremely wet days in the southwest and the central part of Ontario. For temperature indices, cool days and warm night have significant trends in more than 90% of the study area. In general, the spatial variability of precipitation indices is much higher than that of temperature indices. In terms of comparisons between observed and simulated data, results showed large differences for both temperature and precipitation indices. For this region, the regional climate model was able to reproduce historical observed trends in climate indices very well as compared with global climate models. The statistical bias-correction method generally improved the ability of the global climate models to accurately simulate observed trends in climate indices.

Estimates of gridded relative changes in 24-h extreme rainfall intensities based on pooled frequency analysis - Requena, Ana I.; Burn, Donald H.; Coulibaly, Paulin (Journal of Hydrology, 2019)

An overview of river flood forecasting procedures in Canadian watersheds - Zahmatkesh, Zahra; Kumar Jha, Sanjeev; Coulibaly, Paulin; Stadnyk, Tricia (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2019)
Keywords: Ouvrage_Collectif_Numéro1